Improving Junior High School EFL Students’ Reading Literacy through Web-Based Multimodal Text - Wibowo, Mayo Hadi; Sukarno, Sukarno; Wanti, Sri Sarwanti (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2026)
Reading literacy is a critical competency for English as a Foreign Language (EFL) learners; however, Indonesian students consistently perform below international benchmarks as evidenced by Programme for International Student Assessment (PISA) results. This study examined the effectiveness of web-based multimodal text in improving the reading literacy of seventh-grade EFL students at a junior high school in Central Java, Indonesia. A quasi-experimental design with a non-equivalent control group pre-test and post-test structure was employed, involving 52 students (26 experimental, 26 control). The experimental group accessed multimodal reading materials through an integrated website incorporating text, images, audio, video, and tables, while the control group received conventional printed-text instruction. Data were analyzed using the Shapiro-Wilk normality test, independent-samples t-test, Mann-Whitney U test, N-Gain analysis, and Hedges’ g effect size estimation. Results revealed that both groups demonstrated statistically equivalent pre-test performance (p = .852), whereas post-test scores differed significantly (p < .001). The experimental group achieved a mean post-test score of 76.00 (SD = 9.50) compared to 63.00 (SD = 10.20) for the control group. The N-Gain value for the experimental class (g = .59, moderate category) substantially exceeded that of the control class (g = .33, moderate category), and the Hedges’ g effect size of 1.299 indicated a large practical effect. These findings underscore the pedagogical efficacy of multimodal text-integrated websites in fostering reading literacy development among junior high school EFL learners, with implications for instructional design and digital literacy pedagogy in Indonesia and comparable EFL contexts.